Physiological Factors Associated With Declining Repeated Sprint Performance in Hypoxia. Issue 1 (January 2019) - Gatterer, Hannes; Menz, Verena; Untersteiner, Christian; Klarod, Kultida; Burtscher, Martin
Abstract : Abstract: Gatterer, H, Menz, V, Untersteiner, C, Klarod, K, and Burtscher, M. Physiological factors associated with declining repeated sprint performance in hypoxia. J Strength Cond Res 33(1): 211–216, 2019—Performance loss in hypoxia might not only be caused by reduced oxygen availability, but might also be influenced by other factors, as for example, oxidative stress, perceived exertion, or breathing patterns. This study aimed to investigate the influence of these factors on running performance during hypoxic and normoxic shuttle-run sprinting. Eight male amateur soccer players performed shuttle-run sprints in hypoxia (FiO2 ∼14.8%) and normoxia (random order). Each session comprized 3 sets of 5 × 10 seconds back and forth sprints (4.5 m), with recovery times between repetitions and sets of 20 seconds and 5 minutes, respectively. Sprinting distance, acceleration patterns, heart rate (HR) and breathing frequency were measured during each session (Zephyr-PSM Training System). Redox state and lactate concentration ([La]) were determined before and after each session, whereas rating of perceived exertion (RPE) was assessed after the sprint sessions. Overall distance covered was similar during hypoxia and normoxia sprinting (Δ −8.3 ± 14.3 m, 95% CI −20.2 to 3.6, p > 0.05). During the third set, distance tended to be reduced in hypoxia compared with normoxia (169 ± 6 m, 95% CI 164–174 vs. 175 ± 4 m, 95% CI 171–178, p = 0.070). Differences in breathing frequency during sprinting in hypoxia and normoxia were associated with individual reductions in sprinting distance ( r = −0.792, p = 0.019). Despite a somewhat lower running distance during the third set and similar [La], RPE, HR, and redox responses, the preserved overall running distance indicates that the training stimulus might be enhanced in hypoxia compared with normoxia. Alteration of the respiratory patterns during repeated sprinting in hypoxia might be one factor, besides others, responsible for a potential performance loss. It could be hypothesized that respiratory pattern adaptations are involved in potential performance improvements after hypoxia repeated sprint training.